Pan-cancer analysis of SOX2: Prognostic implications and potential as a therapeutic target in immune checkpoint modulation - Shoukai Yu; Lingmei Qian; Liling Xu; Jun Ma (Heliyon)
This study investigates SOX2 genetic, transcriptomic, and epigenetic alterations across over 30 cancer types. Significant downregulation of SOX2 expression was observed in colorectal adenocarcinoma, esophageal carcinoma, rectum adenocarcinoma, stomach adenocarcinoma, and testicular germ cell tumors, whereas its expression was upregulated in cervical squamous cell carcinoma, glioblastoma multiforme, lower grade glioma, lung adenocarcinoma, and lung squamous cell carcinoma.Survival analysis showed that low SOX2 expression correlated with better prognosis in bladder cancer, liver hepatocellular carcinoma, kidney renal clear cell carcinoma, and sarcoma, whereas high SOX2 expression was associated with poor prognosis in lung adenocarcinoma, and lung squamous cell carcinoma, glioblastoma multiforme, lower grade glioma. Although increased immune checkpoint expression is generally linked to poor prognosis, tumors with high SOX2 expression exhibited higher responsiveness to immune checkpoint inhibitors, suggesting that targeting SOX2 may improve immune checkpoint therapy efficacy.The study highlights SOX2 as a key factor in cancer prognosis and immune infiltration across multiple tumor types. Its expression is closely associated with immune-related genes and may serve as both a prognostic biomarker and a therapeutic target. These findings underscore SOX2's potential in regulating immune checkpoints and enhancing cancer immunotherapy.